The EU debt crisis and policy implications for Vietnam - Hoang, Xuan Binh (Journal of International Economics and Management, 2014)
Since 2009, concerns of a sovereign debt crisis developed among fiscally conservative investors concerning several European Union (EU) and euro-zone member states, the so-called PIIGS, i.e. Portugal, Italy, Ireland, Greece, and Spain. That led to a crisis of confidence as well as the widening of bond yield spreads and risk insurance on credit default swaps (CDS) between these countries and other euro-zone members, most importantly Germany. Many observers argue that the creation of the European single currency has contributed to the debt crisis in Europe, and that the future of the Euro is a key concern for investors and markets. Hence, an objective of the paper is to illustrate the origins of the debt crisis, and some policy response in EU. Besides, this study recommends some policies for implementing a strategic plan on public debt, including restructuring debts, resending, or borrowing to finance important and effective programs and projects and ensure national financial security.